Pelimpahan Wewenang dari Dokter Kepada Perawat dalam Melakukan Tindakan Intubasi - Anik Sulistiyowati (Faculty of Law- Hang Tuah University, 2021)
This study examines the legal relationship between nurses and doctors in the work unit in the ICU in carrying out the act of intubation and law enforcement against nurses who intubate. The method used in this research is normative juridical research, namely research using statutory regulations which includes three layers of legal scholarship consisting of a study of legal doctrine, legal theory and legal philosophy. The results of the discussion found that from a legal perspective, the delegation of authorized medical action in hospitals from doctors to nurses has been thoroughly regulated in accordance with the Law. To overcome disputes and the law, it is necessary to have laws and regulations which in detail talk about the legal answers to doctors and nurses in administering health services, both administrative, criminal and civil legal responsibility.